Effect of pH and glycolic acid on corrosion of AA6061 alloy in ethylene glycol–water solution. Issue 1 (7th August 2012) - Zhang, D. Q.; Zhou, L. X.; Rao, C. Y.; Gao, L. X.
<x xml:space="preserve">Abstract</x> The corrosion behaviors of AA6061 alloy in ethylene glycol (EG)–water solution were investigated by weight‐loss test and electrochemical measurement. The surface morphology observation and composition analysis were performed by scanning electron microscopy (SEM) and energy dispersive X‐ray (EDX) spectroscopy. After weight‐loss test, the pH of EG–water solution increased. The presence of glycolic acid (GA) enhanced the corrosion susceptibility of AA6061 alloy. The higher pH value intensified the aggressive action of GA to AA6061 alloy. GA forms a complex with aluminum ions and its negative charge centers of oxygen atom plays a key role for the complex formation.